Simulation of observed temperature field below a building in Bologna, Italy. Issue 4 (16th November 2018) - Focaccia, Sara; Barbaresi, Alberto; Tinti, Francesco
Abstract : Urban settlements, whether single buildings or apartment blocks, influence near-surface ground temperatures. Heat transfer by buildings to the ground must therefore be considered when designing both vertical probes and energy geostructures in urban areas. However, assessment of ground temperature variability in urban areas is still uncommon for shallow geothermal energy purposes, the standard temperature gradient based on climatic conditions usually being employed during the design phase. Yet precise assessment of the heat transfer between buildings, infrastructures and the underground could improve the planning of geothermal systems. This work presents a numerical simulation of a finite-element model of heat transfer to the underground due to both a single building and climate conditions with the aim of reproducing the temperature waves at each depth. An isolated building in Bologna (Italy) was chosen since it allowed exact quantification of its influence on the ground temperature without external interferences. For this purpose, different boundary and initial conditions were applied to the ground thermal model and results were compared with historical data recorded over several years. The idea proposed in the paper for a single building can be considered as the baseline for further ground temperature assessment of wider urban settlements.